Shell Thickness-Dependent Strain Distributions of Confined Au/Ag and Ag/Au Core-Shell Nanoparticles - Feng Liu; Honghua Huang; Ying Zhang; Ting Yu; Cailei Yuan; Shuangli Ye (Advances in Condensed Matter Physics)
The shell thickness-dependent strain distributions of the Au/Ag and Ag/Au core-shell nanoparticles embedded in Al2O3 matrix have been investigated by finite element method (FEM) calculations, respectively. The simulation results clearly indicate that there is a substantial strain applied on both the Au/Ag and Ag/Au core-shell nanoparticles by the Al2O3 matrix. For the Au/Ag nanoparticles, it can be found that the compressive strain existing in the shell is stronger than that on the center of core and reaches the maximum at the interface between the shell and core. In contrast, for the Ag/Au nanoparticles, the compressive strain applied on the core is much stronger than that at the interface and that in the shell. With the shell thickness increasing, both of the strains in the Au/Ag and Ag/Au nanoparticles increase as well. However, the strain gradient in the shell decreases gradually with the increasing of the shell thickness for both of Ag/Au ad Au/Ag nanoparticles. These results provide an effective method to manipulate the strain distributions of the Au/Ag and Ag/Au nanoparticles by tuning the thickness of the shell, which can further have significant influences on the microstructures and physical properties of Au/Ag and Ag/Au nanoparticles.